(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Solar energy is the most significant form of renewable energy, and its efficiency is affected by the angle between the photovoltaic module and the sun. Research has been conducted to enhance its sustainability, cost-effectiveness, and efficiency. The power density of a PV module is highest when it is perpendicular to the sun’s beam. Still, because the sun’s angle with a fixed panel constantly changes, the power density on a fixed PV module is lower than that of the incident sunlight. Additionally, the earth’s orbit and the changing seasons impact irradiance and reduce the output of fixed tilt angle panels. This study aims to estimate the power losses due to fixed PV panels using an analytical model and experimental data and compare the calculated output with data from solar panel installations. The results of this research can help overcome the drawbacks of fixed tilt angles, improve efficiency, increase solar energy production, and reduce dependence on environmentally harmful non-renewable energy sources.